The Human Papillomavirus as a Common Pathogen in Oropharyngeal, Anal and Cervical Cancers. Issue 2 (February 2019) - Otter, S.; Whitaker, S.; Chatterjee, J.; Stewart, A.
Abstract: The burden of human papillomavirus (HPV)-related cancers worldwide is significant. Although the incidence of cervical cancer is decreasing due to cervical screening programmes, the incidences of oropharyngeal, anal and vulval cancers are increasing. The introduction of HPV vaccination programmes in many countries has had an impact on HPV infection rates but due to the time-lag from initial HPV infection to the development of invasive carcinoma, the impact on the incidence of HPV-related cancer will take more time to become evident. This review explores the common aspects of HPV-related cancers and how they differ from their HPV-negative counterparts, both clinically and molecularly. It also covers the implications this has on future treatment strategies, including the possible role of immunotherapy.